Globalization, mass education and technical and vocational education and training : the influence of UNESCO in Botswana and Namibia - Preckler Galguera, Miriam [Verfasser] (Springer, 2018)
"This book assesses the influence of the international organization UNESCO on the development of national Technical and Vocational Education and Training (TVET) systems in the Southern African Community Region (SADC), focusing particularly on Botswana and Namibia. Designed around UNESCO's Better Education for Africa's Rise (BEAR) project, the study is an excellent example of applied policy research. Analysis is from the perspective of key stakeholders including UNESCO headquarters and field offices, Ministries of Education and of Labor, employers and employees, education and training institutions, international partners and more. Both qualitative and quantitative evidence are used to provide a comparative overview, and the author also reveals the current state of data on skills. Readers will discover common goals and challenges across the nations but also a common lack of action to measure the impact and influence that UNESCO's programs have had at a national level, prior to this study. Were the newly implemented educational policies successful or not? If the public policies failed, why was that? These chapters shed light on such questions and how UNESCO's contribution influenced the national development processes, in the context of globalization processes and trends of global mass education." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 1.5 Internationale Organisationen & Institutionen; I 2.3.1 Afrika; Berufsbildung; Berufsbildungssystem; UNESCO; Programm; Botswana; Namibia; Südafrika